Influence of Ducted Propeller on Ro-Ro Vessels for Indonesia Inter-island Transportation - Achdri Fauzi Nugraha Oloan; Prabuditya Bhisma Wisnu Wardhana; Agung Fauzi Hanafi; Yeddid Yonatan Eka Darma (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
These Ro-Ro vessels are the backbone of inter–island transportation in Indonesia and require an efficient propulsion system to reduce fuel consumption and improve maneuvering performance. This study investigates the influence of ducted propellers on Ro-Ro vessels using Computational Fluid Dynamics (CFD) simulations. Four blades fixed pitch propeller configuration with accelerating duct are examined with different radial gaps at the propeller tip to the inner duct surface (0.1m, 0.3m and 0.5m) at rotational speed of 229 rpm and diameter of 4.202 m. the CFD model validation show average deviation of 4.06 % for KT, 7.63 % for 10*KQ and 3.11 % for efficiency compared with the experimental data. It indicated that the numerical approach is sufficiently reliable for further analysis. The open-water test results suggest that adding a duct does not necessarily improve performance. At a 0.10m gap, thrust, torque, and efficiency decrease by 39.3%, 25.7%, and 20.3%, respectively, whereas the 0.5m gap still results in noticeable performance degradation. Wake-field visualization indicates that smaller gaps produce stronger propeller–duct interaction, with more concentrated energy, sharper velocity gradients, and greater instability near the duct outlet. These findings emphasize that duct geometry and tip clearance must be carefully optimized for the vessel’s operating conditions to fully realize the energy benefits of a ducted propeller system on Ro-Ro vessels.